2012
DOI: 10.1002/cjoc.201200627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SnO2‐Sb2O5 Interlayer on Electrochemical Performances of a Ti‐Substrate Lead Dioxide Electrode

Abstract: The Ti/SnO 2 -Sb 2 O 5 /PbO 2 electrode was prepared by electrodeposition method onto Ti substrate with SnO 2 -Sb 2 O 5 interlayer. Microstructure information of SnO 2 -Sb 2 O 5 interlayer and PbO 2 coating was characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). Our study shows that the titanium substrate is completely covered by the SnO 2 -Sb 2 O 5 solid solution interlayer and the interlayer combines the Ti substrate closely with the PbO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the present study, the Cu is in +2 oxidation state and Ti is in +4 oxidation state. The radius of Ti 4+ (0.68 Å) is similar to that of Cu 2+ (0.73 Å), hence copper ions may be incorporated into the lattice of TiO 2 and occupied some of the titanium lattices [25,26]. The charge compensation is mainly achieved by the ionized vacancies especially doubly ionized oxygen vacancies.…”
Section: +mentioning
confidence: 99%
“…In the present study, the Cu is in +2 oxidation state and Ti is in +4 oxidation state. The radius of Ti 4+ (0.68 Å) is similar to that of Cu 2+ (0.73 Å), hence copper ions may be incorporated into the lattice of TiO 2 and occupied some of the titanium lattices [25,26]. The charge compensation is mainly achieved by the ionized vacancies especially doubly ionized oxygen vacancies.…”
Section: +mentioning
confidence: 99%
“…16 Besides, the catalytic performance of the Ti/PbO 2 electrode still has room for improvement. Thus, several efforts have been devoted to further improve its performance in the electrochemical oxidation capability and stability, including inserting the middle layer, 17 . Based on the reports above mentioned, it can be concluded that an appropriate modification can effectively improve the performances of the electrode.…”
Section: 10mentioning
confidence: 99%
“…16 Besides, the catalytic performance of the Ti/PbO 2 electrode still has room for improvement. Thus, several efforts have been devoted to further improve its performance in the electrochemical oxidation capability and stability, including inserting the middle layer, 17 doping with elements (Bi, 18 Co, 19 Fe, 20 F, 21 Ce, 22 Cu, 23 etc. ), compounds (TiO 2 , 24 fluorine resin (FR), 25 etc.)…”
mentioning
confidence: 99%
“…The voltammetric charge quantity (q*), which is related to real surface area and the number of active sites, can reect the electrochemical activity of an electrode. 35 For the same electrode material, larger q* indicates higher electrode activity. We employed the method reported in literature 34 to calculated q* for estimating the electrode activity.…”
Section: Electrochemical Testmentioning
confidence: 99%